Implementation Of The Natural Rural Community Empowerment Program (PNPM) In Ompu Raja Village, East Hutapea Laguboti District-Toba Samosir Regency - Friska M Sinaga (IHSA Institute, 2021)
Indonesia has a poverty problem. The National Program for Independent Rural Community Empowerment is one of the strategies for community empowerment in an effort to accelerate poverty reduction. The SPP (Savings and Loans for Women) program is one of the programs from PNPM-MP that makes women or housewives the target of empowerment. The purpose of implementing the SPP (Savings and Loans for Women) program is to reduce poverty through capital loans for women accompanied by empowerment. This study aims to find out how the implementation of the National Program for Independent Rural Community Empowerment, in particular the implementation of the SPP (Savings and Loans for Women) Program in the study in Ompu Raja Hutapea Timur Village, Laguboti District, Toba Samosir Regency, about what aspects influence the community in participating in the program, how the flow implementation, as well as the obstacles encountered in the ongoing implementation of the program and their solutions.The research method used in this study is a qualitative research method. The research informants were the perpetrators of the National Program for Independent Rural Community Empowerment in Ompu Raja Hutapea Timur Village, namely the Village Head, TPK Chair, Village Community Empowerment Cadre, Person in Charge of Operational Activities, UPK Chair, and several group members who were participants of the SPP program. Data collection techniques were carried out through in-depth interviews and then the results were analyzed qualitatively. From the results of research conducted in the village of Ompu Raja Hutapea east regarding the implementation of the National Program for Independent Rural Community Empowerment, especially the SPP activity program, community participation is more dominated by the economic aspect. The lack of routine meetings for community empowerment by the government also results in obstacles such as delays in loan repayments. However, the community stated that they felt helped by the implementation of the SPP program.